Effect of the Compression Ratio on the Performance of Different Strategies of the Gas Turbine - M. M., Rahman; Ibrahim, Tamir K. (Universiti Malaysia Pahang, 2014)
A clean and safe energy is the greatest challenges in meeting the requirements of green environment. These requirements given way the long time governing authority of steam turbine (ST) in the world power generation, and gas turbine (GT) will replace it. Therefore, it is necessary to predict the characteristics of the GT and optimize its operating strategy by developing a simulation system. Several configurations of the GT plants are proposed by thermal analysis. The integrated model and simulation code for exploiting the performance of GT plant are developed utilizing MATLAB code. The performance code for heavy-duty GT power plants are validated with the Bassily model and the results have been satisfactory. The performance enhancing strategies results show that the higher power output occurs in the intercooler-reheat GT (IHGT) strategy (286 MW). At the compression ratio of 12.4 in the intercooler-regenerative-reheat GT (IRHGT) strategy, the higher (best) thermal efficiency obtained was 50.7 %. While in the IHGT, the lowest thermal efficiency of 22 % to 39.3 % was obtained in the presence of the compression ratio between 3 and 30. Furthermore, the lower fuel consumption (0.14 kg/kWh) occur in the IRHGT strategy. Thus, the compression ratios are strongly influenced on the overall performance of the GT. Keywords: Gas turbine; compression ratio; strategies; performance. INTRODUCTION